Extramammary Paget's disease in two brothers - Xiaoting Zhang; Wanwan Jin; Haibo zhu; Haifeng Yu (Wolters Kluwer Medknow Publications, 2015)
Extramammary Paget's disease (EMPD), which is considered to be an adenocarcinoma of the apocrine glands, is a rare, slow-growing neoplasm. The standard treatment for local EMPD is surgical resection, however, so far, no effective treatment is found for advanced EMPD. Trastuzumab, which is a recombinant monoclonal antibody against the human epidermal growth factor receptor 2 HER2 has been proved to be effective in the treatment of advanced EMPD in some cases where HER2 protein is overexpressed. Herein, we report two cases of EMPD in two brothers. The younger brother who presented as local EMPD on the scrotum received surgical resection and had no recurrence in 15 months following. The older brother suffered from invasive EMPD also on the scrotum with inguinal region multiple metastatic lymph nodes and was treated with combination chemotherapy and Trastuzumab to target HER2 consecutively after a wide surgical excision.